Comparative evaluation of antimicrobian activity of alecrim oil (rosmarinus officinalis) and chemical conservatives used in cosmetic bases - Matos, Janara Camargo (2019)
Microbial contamination has been one of the most important problems of the cosmetic industry, since it may contain microorganisms potentially pathogenic to human health. The choice of substances with antimicrobial activity that will be incorporated into cosmetics to prevent contamination must be made in a judicious manner, in adequate concentrations that guarantee efficacy and safety. Chemical preservatives available on the market have, without exception, some risk of hypersensitivity and therefore efforts have been directed towards the development of natural compounds with antimicrobial activity for the purpose of reducing or replacing traditional chemical preservatives. The essential oils have become gels, creams, lotions andtoday, studies demonstrated their possible use as natural preservative agents. This work aims to verify if the oil of alecrim (Rosmarinus officinalis) is effective as preservative for cosmetic bases compared to chemical preservatives methyl and propyl parabens. The method used was the agar diffusion test where different concentrations of the preservatives were used against Escherichia coli bacteria and the fungus Candida albicans. The results indicated that alecrim essential oil has an intermediate potential of bacteriostatic activity, since it produced inhibition halos, but smaller than those produced by parabens. The research presented important results, although more detailed studies on yield are required, to check cost of production andperformance with other concentrations of this oil to elucidate its true bioactivity, its therapeutic potential and its clinical utility.